Study on road section environmental traffic capacity model and algorithm under double constraints. (October 2016) - Wang, Xiaoxia; Fu, Hui; Lu, Jianfeng; Han, Shuang
Highlights: First, influence factor of road section environmental traffic capacity was analyzed. Second, section environmental traffic capacity optimization model was established. Third, optimization model was solved by using improved augmented Lagrange function. Fourth, case study showed that optimization model and solution method were effective. Abstract: The coordinated development of city traffic and environment is a key research content in traffic field in twenty-first Century. Among them, road section environmental traffic capacity analysis is one of the important research issues. It can provide solid theoretical basis and reliable data support for road network traffic optimization control, road traffic pollution control and city traffic structure optimization. This paper analyzed main factors which impacted environmental traffic capacity from two aspects, including road capacity constraint conditions and road traffic pollution control constraint conditions. Then, road section environmental traffic capacity optimization model was established, and method of improved augmented Lagrange function was used to solve the model. Case study showed that, (1) The environmental traffic capacity optimal model and methodology were effective; (2) In order to ensure road section environmental traffic capacity greater than (or equal to) road capacity, some measures could be taken including adjusting motor vehicle type proportion as well as improving emission characteristics of motor vehicles exhausting pollutants.